2022
DOI: 10.3390/molecules27175428
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Partial and Selective TRPV1 Agonist CPIPC for Alleviation of Inflammatory Pain

Abstract: Transient receptor potential vanilloid 1 (TRPV1) is a non-selective cation channel, predominantly expressed in a subset of peripheral sensory neurons for pain signaling. Topical application of agonist capsaicin for desensitizing TRPV1 currents has been approved for relief of chronic pain. However, the potent TRPV1 capsaicin is not ingestible and even topical capsaicin causes common side effects such as skin irritation, swelling, erythema and pruritus, suggesting that a mild TRPV1 agonist might be helpful for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The determination of the optical band gap involves plotting (hυ) versus (F(R)hυ) 2 , and at the inflection point, drawing a tangent to (F(R)hυ) 2 =0. As illustrated in Figure 1 (inset) (a), (b), and (c), the band gaps for rGO, ZrO 2 , and ZrO 2 /rGO are found to be 1.29, 1.45, and 1.26 eV, respectively [30] …”
Section: Resultsmentioning
confidence: 92%
“…The determination of the optical band gap involves plotting (hυ) versus (F(R)hυ) 2 , and at the inflection point, drawing a tangent to (F(R)hυ) 2 =0. As illustrated in Figure 1 (inset) (a), (b), and (c), the band gaps for rGO, ZrO 2 , and ZrO 2 /rGO are found to be 1.29, 1.45, and 1.26 eV, respectively [30] …”
Section: Resultsmentioning
confidence: 92%
“…The neck and head of compound 2 (Figure 7a) bind to R557. Gao et al (2016) and Dong et al (2022) confirmed that R557 is one of the key residues for the formation of agonism, which explains the agonism of compound 2 . The kind of partial agonist that acts antagonistically to high concentrations of capsaicin has been less studied and has only been similarly reported in vitamin D (Long et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…The ligand-dependent cation channel TRPV1 is a promising target for managing various types of pain disorders [3]. In recent years, an increasing number of studies have focused on discovering TRPV1 antagonists and agonists/desensitizers as therapeutic solutions for chronic, neuropathic and inflammatory pain, but also for migraine and cluster headache [8,19,60]. Unfortunately, the approval of TRPV1 antagonists is hindered due to severe side effects observed in clinical trials, such as hyperthermia.…”
Section: Discussionmentioning
confidence: 99%